Corporate governance in teaching hospitals: a study on a university hospital - Martins, Vidigal; Pereira, Vinícius; Gandolfi, Peterson (Jornal Brasileiro de Economia da Saúde, 2011)
This work portrays the manner that the teaching hospital of the Federal University of Uberlandia (HC-UFU) is facing the integration process of governance practices in their environment, especially the impact that this will suffer during and after the adoption of restructuring measures (REHUF). The hospital serves as a large organization and, in this way, is able to align management practices with governance policies making it necessary to have clarity and soundness in the strategies, processes and structures of these hospitals. In this context, the research helps to clarify some points: the management model of the HC-UFU to adopt governance practices. If so, how they occur in the context of internal processes. To ensure that the analysis of the empirical data is able to contemplate the various aspects that involve the whole object of investigation, the procedures following the assumptions of the exploratory and qualitative research. The guidelines of the research include: degree of centralization/decentralization of administration, form of participation in the decisions of hierarchical levels, degree of autonomy and managerial accountability and reporting process.